Internal sound field reconstruction method based on optimal arrangement of sound monitoring points near the cabin inner surface - Shengguo Shi; Qiang Guo; Huihui He; Xinyu Wang (AIP Advances)
Aiming at the problem of sound field online monitoring and reconstruction inside the cabin, an inner acoustic field reconstruction method based on the optimal arrangement of sound monitoring points near the surface in the cabin is proposed. First, the method determines the truncation order of the acoustic cavity mode based on the analysis frequency range and calculates the sound pressure of each acoustic cavity mode at alternative locations near the inner surface of the cabin acoustic monitoring point. Second, the modal confidence matrix is used as the objective function, and the position of acoustic monitoring points is optimized via quantum particle swarm optimization (QPSO). Finally, the sound field near the interior surface of the cabin is reconstructed based on the optimal arrangement of sound monitoring points, and then the equivalent source method is used to reconstruct the sound field at any position in the cabin. In this paper, the sound field reconstruction accuracy in the cabin is analyzed using the proposed method and the traditional equivalent source method. Besides, the optimum performance of different optimization algorithms is compared. The results show that the proposed method is more accurate than the traditional equivalent source method when the number of monitoring points is the same, and the QPSO algorithm shows the best monitoring point location optimization performance. The effectiveness of the proposed method is further verified by cabin model experiment. Simulation and test results show that the accuracy of acoustic field reconstruction in the cabin based on the proposed method is less than 3 dB in the frequency band below 500 Hz.